The role of the Icelandic horse in Icelandic history and it's image in the Icelandic media - Sigfús Örn Einarsson (2010)
This BA-thesis explores the history of the Icelandic horse and how it has been reflected in the Icelandic media since the mid 1800s. More specifically, it looks at how the image of the Icelandic horse has changed, parallel to its changing role in society following industrialization in Iceland. This is linked to how the Icelandic media influenced the formation of the Icelandic society in the 19th and the 20th century.